2021
DOI: 10.1002/ange.202102106
|View full text |Cite
|
Sign up to set email alerts
|

Precise Identification and Characterization of Catalytically Active Sites on the Surface of γ‐Alumina**

Abstract: g-alumina is one of the oldest and most important commercial catalytic materials with high surface area and stability.These attributes enabled its use as the first commercial large-scale heterogeneous catalyst for ethanol dehydration. Despite progress in materials characterization the nature of the specific sites on the surface of g-alumina that are responsible for its unique catalytic properties has remained obscure and controversial. By using combined infrared spectroscopy, electron microscopya nd solid-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…CO adsorption at room temperature on thermally activated sample does not lead to any discernible CO signatures. This indicates that no penta Al sites are available on the surface since these are the only sites that can adsorb CO strongly under ambient conditions on alumina surfaces [43]. This result is further consistent with high-field solidstate 27Al NMR measurements (Fig.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…CO adsorption at room temperature on thermally activated sample does not lead to any discernible CO signatures. This indicates that no penta Al sites are available on the surface since these are the only sites that can adsorb CO strongly under ambient conditions on alumina surfaces [43]. This result is further consistent with high-field solidstate 27Al NMR measurements (Fig.…”
supporting
confidence: 86%
“…Furthermore, a new C-O stretching band appears ~2,220 cm -1 . We have previously shown that this band corresponds to CO directly adsorbed on tetra-Al sites [43]: indeed, Ce+3 dispersed on these sites prevent CO adsorption on them. Once they are removed by O2 treatment, these sites become available for CO adsorption.…”
mentioning
confidence: 81%
“…On γ-Al 2 O 3, the IR bands of the surface hydroxyl groups were 3837, 3700, 3604, 3549, and 3501 cm –1 , and a wide band was less than 3500 cm –1 . These hydroxyl groups represented the −OH in the forms of terminated, bridged, or multiple coordination on different Al 2 O 3 crystal planes . In contrast, new bands at ∼3730 and 3783 cm –1 were observed for Pd–Pt/Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Kovarik * , K. Khivantsev * , J. Szanyi * * Institute for Integrated Catalysis, Pacific Northwest National Laboratory, Richland, Washington, USA Transition aluminas are used in catalytic applications as catalysts and catalytic supports due to their excellent thermal stability, ability to maintain high surface area, and most importantly their unique surface properties [1]. Understanding the surface properties of transition aluminas has been the subject of extensive research, and while much progress has been made, the actual surface structure of transition aluminas remains only conceptually understood [1,2,3]. A detailed nature of bonding environment has been mostly inaccessible to surface science techniques because of high degree of structural disorder, as well as inherent difficulties associated with studying high surface-area materials.…”
Section: Application Of 4d Stem and Dpc Techniques To Study Surface R...mentioning
confidence: 99%